Antitumor Activities of Flavonoids and Their Biological Activities on Human Health - Moheisen, Hassan Mahmoud (Journal of medical and pharmaceutical sciences, 2019)
Flavonoids are ubiquitous in photosynthesising cells and are commonly found in fruit, vegetables, nuts, seeds, stems, flowers, tea, wine, propolis and honey. Therefore, a significant quantity is consumed in our daily diet. These flavonoids are variously associated with the sensory and nutritional quality of our plant foods. For centuries, preparations containing these compounds as the principal physiologically active constituents have been used to treat human diseases. There have been many bioassay guided searches for cytotoxic antitumour agents in plants especially those known to be used in folk medicine for this purpose. This has led to the isolation and identification of quite a large number of active constituents from all the diferent flavonoid classes, e.g. catechins, flavans, dihydrochalcones, chalcones, flavanones, dihydro- flavonols, flavones, biflavonoids and flavonol.The purpose of the present review is to discuss recent developments in the biochemistry and medicinal aspects of the flavonoids. It is already well established that flavonoids make some contribution to disease resistance. Perhaps the most active area of flavonoid research at the present time is in the possible medicinal contribution that flavonoids make to human health, It is well known that some flavonoids can act as anti-spasmolytic agents, antibacterial activity, hepatoprotective agents and prevention of malaria. Recent research on the biological properties of flavonoids will therefore be a further subject of the present review. The activity of 17- β- estradiol, for example, have a pharmacologicalefficacy, at optimal concentrations, which is equivalent to the natural hormone. The compounds: 4´,7´´- di- O- methylamentofavone and 7´´- O- methylrobustafavone, were significantly cytotoxic against human cell lines including breast, lung, colon and prostate cancer, fibrosarcoma, glibostoma, oral epidermoid carcinoma and leukemia. Amongst the favonols, quercetagetin 6,7,3´ ,4´- tetramethyl ether, was found to show significant cytotoxicity against murine leukaemia, human non- small cell lung cancer, human colon cancer, and KB tumour cells.
Keywords: flavonoids; tumors; health